ANALISA.PENGENDALIAN.INTERN DALAM PERSEDIAAN OBAT UNTUK PASIEN PENGGUNA BPJS KESEHATAN. DI RSUD Dr. H. MOH. ANWAR KABUPATEN SUMENEP - Jimat, Syaiful; Pratiwi, Ni Made Ida; Nasution, Ute Ch (Universitas 17 Agustus 1945 Surabaya, 2018)
This.study.aims.to.determine.the.system and.procedure of drug supply in Dr. H. Moh. Anwar, Sumenep Regency. The research method.used by the author is qualitative.with the form of research used that is descriptive. The results of the data analysis showed.that the drug supply system in the Pharmacy department at Dr. RSUD H. Moh. Anwar of Sumenep Regency is already good enough in providing medicines. This causes the existing system to be said to be complete with the separation of duties and the arrangement of supplies which are supported by complementary documents. Recording that has been done can be said to be good to divert things that are detrimental to the Hospital. Supplies Medicines in pharmacy have been done with good and correct systems and proceduresKeywords : Control System, inventory Management and Inventory.